Investigation on Environmental Alpha Radioactivity around Jaduguda Uranium Mine – An Experimental Study along Subarnarekha River - Das, Biswajit; Deb, Argha (Modern Advances in Geography, Environment and Earth Sciences Vol. 7, 2021)
Mining effect is expected to increase the radioactivity level in the environmental matrices at the mine areas. Presence of a river nearby the mine areas contributes to a chance of spreading of the enhanced level of radioactive contamination considerably into the areas. Our previous work already showed that alpha radioactivity of water of Subarnarekha River is enhanced due to the effect of Jaduguda uranium mine. The question that consequently pops up is whether the associated materials like soil, sand and gravel along the river path of Subarnarekha will also be contaminated with radionuclides. Such contamination will cause severe harm to public health because these objects are often used as building materials. For this, a large number of samples of soil, sand, stone and gravel have been collected from different locations along the Subarnarekha river path starting from the area near Jaduguda upto the river mouth and measured their alpha radioactivity using LR-115 SSNTDs. The measured alpha radioactivity ranges from 55 to 2116 Bq. Kg-1, 283 to 760 Bq. Kg-1, 933 to 2075 Bq. Kg-1, and 979 to 1924 Bq. Kg-1, for gravel, stone, sand and soil samples, respectively. In majority of the sites the soil samples show highest radioactivity among all the samples, and the average radioactivities of the soil & the sand samples are greater than those of gravel & stone samples. It is seen that the alpha radioactivity of soil and sand samples are correlated with the distance from Jaduguda along Subarnarekha river, but that for the samples of gravel and stone it is not so. The present study is the first ever attempt to measure and analyse the radioactivity patterns of soil, sand, stone & gravel along the Subarnarekha river path. This study reveals some noticeable facts that are not only important from the academic point of view but also crucial for the health of the local people.